Tindak Tutur Ekspresif pada Remaja Dalam Interaksi Sosial di Universitas Trunojoyo Madura - Eisya Nur Faj'ria; Eka Susylowati; Hapsari Puspitarini; Fitriyatuz Zakiyah (Journal of Social, Culture, and Language, 2025)
Language function not only as a channel for transmitting information but also as a means of performing actions, including expressing the speaker’s emotions, attitudes, and feelings, as stated in the speech act theory. Within the university context, students’ daily interactions often display emotional and interpersonal expressions that can be analyzed through expressive speech acts. This study aims to explore the forms and functions of expressive speech acts used by students at Universitas Trunojoyo Madura in their social interactions, a subject that has received limited attention in Indonesian academic research. Using a qualitative descriptive approach, data were collected through observation, recording, and note-taking, while the analysis was guided by Searle’s classification of illocutionary acts. The findings show that expressive speech among students appear in various forms, such as expressions of surprise, fear, joy, praise, and humor. These utterances reflect not only the emotional state of the speakers but also their efforts to foster closeness, solidarity, and positive social relations in communication. Overall, the study highlights the significant role of expressive speech acts in shaping students’ communication patterns and sustaining harmonious social interactions within the university environment.